2022
DOI: 10.3390/ph15070841
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized N-(4-Bromophenyl)furan-2-carboxamides via Suzuki-Miyaura Cross-Coupling: Anti-Bacterial Activities against Clinically Isolated Drug Resistant A. baumannii, K. pneumoniae, E. cloacae and MRSA and Its Validation via a Computational Approach

Abstract: N-(4-bromophenyl)furan-2-carboxamide (3) was synthesized by the reaction furan-2-carbonyl chloride (1) and 4-bromoaniline (2) in the presence of Et3N in excellent yields of 94%. The carboxamide (3) was arylated by employing triphenylphosphine palladium as a catalyst and K3PO4 as a base to afford N-(4-bromophenyl)furan-2-carboxamide analogues (5a-i) in moderate to good yields (43–83%). Furthermore, we investigated the in vitro anti-bacterial activities of the respective compounds against clinically isolated dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[29][30][31] Our research team employed SMC coupling to synthesize carboxamides and carboxylate derivatives, which were then tested for their in-vitro anti-bacterial properties against WHO-listed extremely resistant bacterial strains, aiming to identify potential therapeutic candidates. [32][33][34][35] In the present study, both the ESBL producing E. coli and MRSA were resistant to commonly used antibiotics including penicillins, cephalosporins, and beta-lactam inhibitors. The anti-bacterial activity of butyl 2-bromoisonicotinate molecules and its derivatives against ESBL-producing E. coli ST405 and MRSA.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[29][30][31] Our research team employed SMC coupling to synthesize carboxamides and carboxylate derivatives, which were then tested for their in-vitro anti-bacterial properties against WHO-listed extremely resistant bacterial strains, aiming to identify potential therapeutic candidates. [32][33][34][35] In the present study, both the ESBL producing E. coli and MRSA were resistant to commonly used antibiotics including penicillins, cephalosporins, and beta-lactam inhibitors. The anti-bacterial activity of butyl 2-bromoisonicotinate molecules and its derivatives against ESBL-producing E. coli ST405 and MRSA.…”
Section: Discussionmentioning
confidence: 59%
“…At the same time, the amides behave as a hydrophilic binding site against bacterial enzyme proteins, which may cause death or make static growth, leading to good inhibitory activity. 36 Further, we studied the N, O, and S heterocycles carboxamides like N-(4-bromophenyl)furan-2-carboxamide, 32 2-aryl-4-chlorophenyl-5-arylthiophene-2-carboxylates 34 4-bromo-N-(5-methyl-1H-pyrazol-3-yl) benzamide, 35 N-(4-methylpyridin-2-yl) Thiophene-2-Carboxamide 37 to study the effectiveness of these scaffolds and found effectiveness against different resistant strains of E. coli, A. baumannii, S. enterica, E. cloacae, S. aureus and K. pneumoniae. We found that heterocyclic carboxamides are pivotal in anti-bacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity of the compounds was determined by agar well diffusion assay against ESBL-producing E. coli described previously [ 28 ]. In short, 0.5McFarland bacterial suspension was inoculated on the Mueller Hinton Agar plate, and a sterile 6 mm cork borer was used to make wells on each plate.…”
Section: Methodsmentioning
confidence: 99%
“…Microbroth dilution assay determined different compounds’ MIC (% w / v ) [ 28 ]. Two to three isolated colonies were mixed in 20mL of double-strength lysogeny broth (LB) medium in 50 mL of falcon tubes and incubated at 37 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation